Counteraction of Skin Inflammation and Aging or Cancer by Polyphenols and Flavonoids from Polypodium leucotomos and Xanthohumol - Philips, Neena; Bynum, David; Hwang, Hyeondo (Anti-Inflammatory & Anti-Allergy Agents in Medicinal Chemistry, 2010)
Skin aging is intrinsic and among the main causes there is the exposure to solar ultraviolet (UV) radiation, which can also lead to skin cancer. The photo-aging or cancer mechanisms include inflammation, oxidative stress from reactive oxygen species (ROS), altered expression of genes, and direct or indirect damage to cellular molecules. The primary inflammatory mediators are interleukin-1 (IL-1), interleukin -6 (IL-6), tumor necrosis factor-alpha (TNF-α) and cycloxygenases (COX)/prostaglandins (PGs). Skin aging and cancer manifests as damage to the extracellular matrix (ECM) composed predominantly of collagen, elastin, and fibrillin. The cells responsible for ECM alterations include epidermal keratinocytes, dermal fibroblasts, and neutrophils. The remodeling of the ECM, primarily as the consequence of inflammation, in skin aging or cancer is from reduced synthesis and increased expression of matrixmetalloproteinases (MMPs). The MMPs degrade the extracellular matrix (ECM) and facilitate metastasis. The predominant classes of MMPs include collagenases (MMP-1, 3) and gelatinases (MMP-2, 9) that degrade the interstitial collagen and basement membrane. In addition, the cellular inhibitors of MMPs, tissue inhibitors of MMPs (TIMPs), and a primary regulator of extracellular matrix (ECM) deposition, transforming growth factor-β (TGF-β), are lowered in skin aging and/or cancer. Polyphenols and flavonoids may be the solution to inflammation associated with skin aging and cancer. P. leucotomos (a tropical fern plant) extract is rich in polyphenols with properties to counteract skin aging mechanisms from its antioxidant and anti-inflammatory properties: it inhibits oxidative stress, lipid peroxidation, dermal mast cell infiltration, inflammatory cytokines, DNA damage, and UV induced tumors. The anti-inflammatory effects of xanthohumol, a flavanoid, include inhibition of COX/PGs and NF-kB transcription factor that is associated with pro-oxidation and inflammation. Further, xanthohumol inhibits nitric oxide production. In addition to the inhibition of inflammatory mediators, polyphenols and flavonoids may stimulate anti-inflammatory mediators such as TGF-β for skin health.
Keywords: Extracellular matrix